1999
DOI: 10.1046/j.1365-263x.1999.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Vegetarianism and dental fluorosis among children in a high fluoride area of northern Tanzania

Abstract: The significantly lower prevalence and severity of dental fluorosis among the vegetarian group compared to the nonvegetarians would seem to be related to diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 17 publications
1
25
2
2
Order By: Relevance
“…It is known that a vegetarian diet results in more alkaline urine which, in turn, leads to increased urinary fluoride excretion [Whitford, 1990[Whitford, , 1996. In support of these physiological findings, Awadia et al [1999] reported that, in a Tanzanian population, non-vegetarians had a 7 times greater risk of developing dental fluorosis compared with vegetarians. Thus, caution is needed when using the findings in the present publication in populations consuming a 'nonwestern ised' diet.…”
Section: Discussionmentioning
confidence: 71%
“…It is known that a vegetarian diet results in more alkaline urine which, in turn, leads to increased urinary fluoride excretion [Whitford, 1990[Whitford, , 1996. In support of these physiological findings, Awadia et al [1999] reported that, in a Tanzanian population, non-vegetarians had a 7 times greater risk of developing dental fluorosis compared with vegetarians. Thus, caution is needed when using the findings in the present publication in populations consuming a 'nonwestern ised' diet.…”
Section: Discussionmentioning
confidence: 71%
“…In North Tanzania, a study of 165 schoolchildren (aged 6-18 years) found that the prevalences of moderate (TFI score 1-4 score) and severe (TFI score 5-9) dental fluorosis were 67%, and 21% respectively among vegetarian children, and were lower than the prevalences of moderate and severe dental fluorosis among non-vegetarian children (95% and 35% respectively) [25]. This could explain the negative significant associations between the level of consuming plant protein and dental fluorosis in the current study.…”
Section: Discussionmentioning
confidence: 97%
“…O risco de desenvolvimento de fl uorose dentária parece ser bastante menor entre vegetarianos 18 , contudo, foi encontrado apenas um estudo sobre este tema, o que não permite tirar conclusões definitivas. Além disso, outros fatores (além da dieta) contribuem para o aparecimento da fl uorose, como a ingestão de dentifrí-cios e soluções para bochechos, e mesmo a ingestão de água, bebidas e alimentos processados industrialmente em regiões abastecidas por água fl uoretada 27 , e estas variáveis não foram controladas pelo estudo analisado nesta revisão.…”
Section: Resultsunclassified